Climate warming amplified the 2020 record-breaking heatwave in the Antarctic Peninsula - González Herrero, Sergi; Barriopedro Cepero, David; Trigo, Ricardo M.; Albert López-Bustins, Joan; Oliva, Marc (Communications Earth & Environment, 2022)
February 2020 was anomalously warm in the Antarctic Peninsula region and registered one of the most intense heatwaves ever recorded in Western Antarctica. The event featured unprecedented regional mean temperature anomalies (+4.5 degrees C) over the Antarctic Peninsula between 6 and 11 February 2020 and the highest local temperature of the continental Antarctic region. Taking flow analogs of the event from past (1950-1984) and recent (1985-2019) periods of the ERA5 reanalysis, here we quantify the role of recent climate change in the magnitude of this 6-day regional heatwave. Results show that 2020-like heatwaves over the Antarctic Peninsula are now at least similar to 0.4 degrees C warmer than in the past period, which represents a similar to 25% increase in magnitude. Given the observed atmospheric circulation conditions, the probability of experiencing 6-day regional mean anomalies above similar to 2 degrees C has increased ten times since 1950-1984. The aggravated severity of the event can be largely ascribed to long-term summer warming of the Antarctic Peninsula rather than recent atmospheric circulation trends.